2016
DOI: 10.1016/j.phymed.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effect of eugenol envolves G2/M phase abrogation accompanied by mitochondrial damage and clastogenic effect on cancer cell in vitro

Abstract: These promising results presented herein shed new light on the mechanisms of action of EUG suggesting a possible applicability of this phenylpropanoid as adjuvant in anti-cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The analysed results show a significant increase in phosphorylated Erk1/2 after 48 and 72 h of treatment with CBE ( Figure 5A,C), as well as a time and dose-dependent increased production of ROS, lipid peroxides, and reactive nitrogen species (Figure 2). It is clear that eugenol, as part of the clove buds extract, represent a major substance associated with ROS production and lipid peroxidation [45,46]. It is also suggested that ROS can be involved also in activation of the other members of MAPK signalling including JNK and p38-MAPK [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The analysed results show a significant increase in phosphorylated Erk1/2 after 48 and 72 h of treatment with CBE ( Figure 5A,C), as well as a time and dose-dependent increased production of ROS, lipid peroxides, and reactive nitrogen species (Figure 2). It is clear that eugenol, as part of the clove buds extract, represent a major substance associated with ROS production and lipid peroxidation [45,46]. It is also suggested that ROS can be involved also in activation of the other members of MAPK signalling including JNK and p38-MAPK [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Eugenol inhibits the breast cancer related oncogenes, NF-κB and cyclin D1 and up-regulates the cyclin-dependent kinase inhibitor p21 WAF1 protein; On the other hand, eugenol was also cytotoxic to non-cancer cell line MCF 10A (human breast epithelial) with IC 50 value of 2.2 μM [ 50 ]. Júnior et al [ 51 ] also assessed the cytotoxicity of eugenol in the μM range on MDA-MB-231, MCF-7, SIHA (human cervix carcinoma), SK-Mel-28 (human melanoma) and A2058 (human melanoma) cells; it was accompanied by ROS production, causing G2/M phase block and, consequently, clastogenesis. Eugenol also induced downregulation of PCNA (proliferation cell nuclear antigen), decreased the mitochondria transmembrane potential and upregulated Bax [ 51 ].…”
Section: Cytotoxic and Antitumor Effects Of Eugenol And Its Relatimentioning
confidence: 99%
“…Júnior et al [ 51 ] also assessed the cytotoxicity of eugenol in the μM range on MDA-MB-231, MCF-7, SIHA (human cervix carcinoma), SK-Mel-28 (human melanoma) and A2058 (human melanoma) cells; it was accompanied by ROS production, causing G2/M phase block and, consequently, clastogenesis. Eugenol also induced downregulation of PCNA (proliferation cell nuclear antigen), decreased the mitochondria transmembrane potential and upregulated Bax [ 51 ].…”
Section: Cytotoxic and Antitumor Effects Of Eugenol And Its Relatimentioning
confidence: 99%
“…Al‐Sharif, Remmal, and Aboussekhra () displayed eugenol triggered apoptosis in breast cancer cells through E2F1/surviving down‐regulation. Junior et al () elucidated that the apoptotic effect of eugenol involved G2/M phase abrogation accompanied by mitochondrial damage and clastogenic effect on cancer cells in vitro. With respect to lung cancer, Li et al () unraveled the tumor suppressive effects of eugenol on cell proliferation, migration, and invasion partially via inhibition of PI3K/Akt pathway and MMP activity (Fangjun & Zhijia, ), However, the importance of eugenol for potential clinical applications on NSCLC was tremendously compromised due to the suspicious artifacts associated with cell culture.…”
Section: Introductionmentioning
confidence: 99%